Development Approach for Legal Instruction in Digital Age by Applying Streaming Services and Online Media - Ulanwong, Surachai (CRRU Law, Political Science and Social Science Journal, 2025)
This research aimed to study the presentation of laws on streaming service platforms, investigate opinions of students of the Faculty of Law, Chiang Rai Rajabhat University on the application of streaming services and online media in law education, and explore the development of law education in the digital era using streaming services and online media. This research was a mixed-method study that focused on collecting qualitative data from studies and data gathered from streaming services and online media, as well as quantitative data collected through questionnaires from a sample of 272 law students at Chiang Rai Rajabhat University. The findings for this research revealed that the content of laws presented in series, movies, and documentaries on streaming service platforms. These media presented various cases that could be linked to civil law, criminal law, and public law, covering adjudication systems, dispute issues, the burden of proof, witness examination, case judgments, and enforcement. Moreover, students were interested and prepared to learn legal content from legal movies, series, and real crime documentaries. Most students were interested in activities and learning styles in the form of lectures, which indicated that students still primarily emphasized receiving information from the instructor. Therefore, based on the results of this research, the development approach for law education in the digital era using streaming services and online media could emphasize that instructors should consider using a blended teaching approach, focusing on lectures combined with other learning styles, and selecting teaching materials that were consistent with the content and legal issues for learning by using streaming services and online media appropriate to the content and the learners.